Towards a Desktop-AR Prototyping Framework: Prototyping Cross-Reality Between Desktops and Augmented Reality - Cools, Robbe; Gottsacker, Matt; Simeone, Adalberto; Bruder, Gerd; Welch, Greg; Feiner, Steven (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
Augmented reality (AR) head-worn displays (HWDs) allow users to view and interact with virtual objects anchored in the 3D space around them. These devices extend users' digital interaction space compared to traditional desktop computing environments by both allowing users to interact with a larger virtual display and by affording new interactions (e.g., intuitive 3D manipulations) with virtual content. Yet, 2D desktop displays still have advantages over AR HWDs for common computing tasks and will continue to be used well into the future. Because of their not entirely overlapping set of affordances, AR HWDs and 2D desktops may be useful in a hybrid configuration; that is, users may benefit from being able to work on computing tasks in either environment (or simultaneously in both environments) while transitioning virtual content between them. In support of such computing environments, we propose a prototyping framework for bidirectional Cross-Reality interactions between a desktop and an AR HWD. We further implemented a proof-of-concept seamless Desktop-AR display space, and describe two concrete use cases for our framework. In future work we aim to further develop our proof-of-concept into the proposed framework.